Liver transplant for patients outside Milan criteria - Levi Sandri, Giovanni Battista; Rayar, Michel; Qi, Xingshun; Lucatelli, Pierleone (Translational Gastroenterology and Hepatology, 2018)
Hepatocellular carcinoma (HCC) is one of the most indication to Liver Transplantation (LT). Milan criteria are worldwide accepted as the gold standard for LT indication for HCC. Nevertheless, expanded criteria are often used to transplant patient outside Milan. We described the most important proposed criteria outside Milan criteria. From the University of California San Francisco, to the Toronto criteria. From East to Western, and for living donor liver transplantation. In order to achieve similar results the downstaging strategy is more frequently used and for patients with locally advanced HCC. Carefully selected patients beyond the traditional criteria for transplantation may achieve excellent LT outcomes through a planned, multidisciplinary approach to treatment.